2019
DOI: 10.1155/2019/3092514
|View full text |Cite
|
Sign up to set email alerts
|

Fuzzy Emergency Model and Robust Emergency Strategy of Supply Chain System under Random Supply Disruptions

Abstract: For random distributors under supply disruptions caused by emergency incidents, a fuzzy emergency model and a robust emergency strategy of the supply chain system are studied. First, for a kind of supply chain system composed of a strategic manufacturer, a backup manufacturer, and multiple distributors, the basic emergency models, including the inventory models and a total cost model, are constructed under random supply disruptions. Then, based on the Takagi-Sugeno fuzzy system, the basic emergency models of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
(43 reference statements)
0
9
0
Order By: Relevance
“…A comparison between the average annual cost modeling method and the discounted costs modeling method was made. Zhang et al (2019) studied a system comprised of a manufacturer, a backup manufacturer, and multiple distributors. The distributors could receive goods from the backup manufacturer and/or other distributor, and a robust emergency strategy was designed to tackle the supply disruption problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A comparison between the average annual cost modeling method and the discounted costs modeling method was made. Zhang et al (2019) studied a system comprised of a manufacturer, a backup manufacturer, and multiple distributors. The distributors could receive goods from the backup manufacturer and/or other distributor, and a robust emergency strategy was designed to tackle the supply disruption problem.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Giri and Bardhan [5] built a two-echelon supply chain under uncertain demand and supply disruption, where the penalty contract mechanism is applied to achieve supply chain coordination. Zhang et al [4] adopted a procurement strategy with backup sourcing under stochastic supply and demand, where the game-theoretic framework is involved to explore optimal decisions of the players. Nevertheless, it can be concluded that these papers simply assume backup supplier to be initiated after supply disruption is realized, which do not distinguish WPP-SR from WPP-DR. Additionally, in their studies, partial disruption is excluded from supply disruption, which certainly merits additional attention.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In practice, the upstream supply process is highly vulnerable to supply disruption, ranging from major breakdowns because of natural or man-made disasters (e.g., earthquakes and floods) to minor interruptions due to material contamination and labour problems [1,2]. As a result, the supply process may entirely halt (completely shut down) or the output differs in the order size (partially disrupted), leading to supply shortage, loss of goodwill, and the collapse of supply chain, which has already been viewed as one of the major challenges to supply chains success and caused massive economic consequences [3,4]. For example, the volcanic eruption in Iceland in March 2010 caused the air cargo transportation to be completely paralyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al studied a basic emergency model under random supply disruption for a supply chain system composed of a strategic manufacturer, a spare manufacturer, and multiple distributors, and proposed a new fuzzy robust emergency strategy by defining a discrete piecewise Lyapunov function [16].…”
Section: Introductionmentioning
confidence: 99%